Lumbar Puncture Increases Risk of Lumbar Degenerative Disc Disease: Analysis From the Rochester Epidemiology Project. Issue 20 (15th October 2020) - Moinuddin, F. M.; Wahood, Waseem; Yolcu, Yagiz; Alvi, Mohammed Ali; Goyal, Anshit; Frank, Ryan D.; Bydon, Mohamad
Abstract : Supplemental Digital Content is available in the text